Remoção de sulfeto em sistemas anaeróbios de tratamento de esgotos por desnitrificação autotrófica associada a microaeração - Brito, Jéssyca de Freitas Lima (2020)
The present work evaluated autotrophic denitrification, via nitrate and nitrite, associated with microaeration, as an in situ strategy for the removal of dissolved and gaseous sulfide produced during anaerobic treatment of sulfate-containing sewage. For this, the effect of different concentrations of nitrate (50-300 mg·L-1) and nitrite (50-150 mg·L-1) as well as different microaeration flow rates (0.1-04 mL air·min-1) and application points (headspace and feeding line) on the removal of dissolved and gaseous sulfide fractions produced in a lab-scale anaerobic reactor (3.0-L working volume and 8-h hydraulic retention time), fed with synthetic sewage containing sulfate (1 g COD·L-1 and 100 mg SO4 2-·L-1), was investigated. In addition, the effect of biogas recirculation (27 L·d-1) through the sludge blanket was evaluated when the reactor was microaerated in the headspace (0.2 and 0.4 mL air·min-1) or supplemented with nitrate (50 mg·L-1), and, then, the association of the two technologies (autotrophic denitrification and microaeration) for the removal of gaseous and dissolved sulfide. Finally, the kinetics of sulfide removal by nitrate and nitrite addition in the presence of organic matter was evaluated. The addition of nitrate or nitrite, individually to the reactors, had a positive impact on the removal of dissolved sulfide, whose best results were achieved with the concentration of 300 mg NO3 -·L-1 (97% lower than the expected dissolved sulfide concentration) and 150 mg NO2 -·L-1 (complete removal of dissolved sulfide). However, this strategy was not so effective for gas sulfide removal. Both methanogenesis and sulfidogenesis were not impaired by the addition of different nitrate or nitrite concentrations, because COD was abundant. Therefore, probably, the main mechanism of sulfide removal was autotrophic denitrification, which occurred effectively even in the presence of high organic matter content. On the other hand, microaeration was an excellent technology for gaseous sulfide removal, achieving efficiencies of 100% when added to the headspace, at a flow rate of 0.2 mL air·min- 1. However, for dissolved sulfide, there were no significant removals. Biogas recirculation had a positive effect on the removal of dissolved sulfide, but ultimately compromised the complete removal of gaseous sulfide when a flow less than 0.4 mL air·min-1 was injected into the headspace. The association of the two studied processes, autotrophic denitrification and microaeration, favored the complete elimination of dissolved and gaseous sulfide produced in the anaerobic reactor. Finally, with the kinetic studies, it can be noticed that the increase of nitrate/nitrite concentration directly interfered in the autotrophic denitrification process. In addition, it was found that the excess of nitrate/nitrite added leads to sulfate formation rather than elemental sulfur, and therefore should be avoided. Finally, the presence of excess organic matter can negatively impact sulfide removal via autotrophic denitrification.